( 6 6 4 ) − ( 1 7 ) ( 6 5 4 ) + ( 2 7 ) ( 6 4 4 ) − ( 3 7 ) ( 6 3 4 ) + ( 4 7 ) ( 6 2 4 ) − ( 5 7 ) ( 6 1 4 ) = ( k n )
If the equation above holds true for k > ⌊ 2 n ⌋ , then which of the following is a possible value of n − k .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
We have,
( 1 − x 1 0 ) 7 = 1 − ( 1 7 ) x 1 0 + ( 2 7 ) x 2 0 − ( 3 7 ) x 3 0 + ( 4 7 ) x 4 0 − ( 5 7 ) x 5 0 + ( 6 7 ) x 6 0 − ( 7 7 ) x 7 0 ,
and,
( 1 − x ) − 7 = 1 + ( 6 7 ) x + . . . + ( 6 1 4 ) x 8 + . . . + ( 6 2 4 ) x 1 8 + . . . + ( 6 6 4 ) x 5 8 + . . .
Now, if we multiply these two equations, then we can see that the above summation is nothing but the coefficients of x 5 8 in the final equation.
Thus, we need to find the coefficient of x 5 8 in ( 1 − x 1 − x 1 0 ) 7 .
Expanding, we need to find coefficient of x 5 8 in ( 1 + x + x 2 + . . . + x 9 ) 7 .
To solve the above question we can find the number of solutions of the equation: x 1 + x 2 + . . . + x 7 = 5 8 , where each 0 ≤ x i ≤ 9
We'd like to use the formula for positive integer solutions here, but since the x i s are limited, it would be incorrect.
So, after a bit of manipulation, we get: ( 9 − x 1 ) + ( 9 − x 2 ) + . . . + ( 9 − x 7 ) = 5 ⇒ y 1 + y 2 + . . . + y 7 = 5 , where each 0 ≤ y i ≤ 9
Now the maximum allowed value of y i is 5 , therefore we can simply use the formula for positive integer solution, a.k.a. Beggar's Method to get ( 7 − 1 5 + 7 − 1 ) = ( 6 1 1 )
Therefore, n − k = 5